Interatomic Interactions in Binary Plutonium Compounds. - Fertikov, Valery; Grigory, Seguru (European Journal of Applied Sciences, 2021)
Based on the reference data on the density of substances in a condensed state, calculations of the concentration of electrons, the concentration of nucleons and the compaction coefficient for binary plutonium compounds are presented. It is proposed to use the concentration of electrons and the concentration as the structural characteristics of materials. It is shown that the concentration of electrons and the concentration of nucleons are applicable to characterize the structures of substances: in solid, liquid and gaseous states. The use of correlation analysis showed the uniqueness of the compaction of plutonium trichlorides and tribromides.